RBG's brave & brilliant women : 33 Jewish women to inspire everyone - Epstein, Nadine (Delacorte Press, 2021)
Profiles thirty-three Jewish women, who lived from biblical to modern times, curated by Supreme Court Justice Ruth Bader Ginsberg, discussing their leadership, bravery, character, and accomplishments. Includes essays that discuss the importance of having female role models and that encourage readers to push for women's rights.